Experiences, utilisation and outcomes of maternity care in England among women from different socio‐economic groups: findings from the 2010 National Maternity Survey. (17th September 2014) - Lindquist, A; Kurinczuk, JJ; Redshaw, M; Knight, M
<x xml:space="preserve">Abstract</x> Objective The objective of this analysis was to explore the healthcare‐seeking behaviours and experiences of maternity care among women from different socio‐economic groups in order to improve understanding of why socially disadvantaged women have poorer maternal health outcomes in the UK. Design Secondary analysis of a national survey of women conducted 3 months after they had given birth. Setting England. Sample A total of 5332 women. Methods Logistic regression analysis to investigate differences in outcomes among different socio‐economic groups, classified by the Index of Multiple Deprivation (IMD). Main outcome measures Healthcare‐seeking behaviours, outcomes and experiences of maternity care. Results With each increase in IMD quintile (decrease in socio‐economic position), women were shown to be 25% (adjusted odds ratio [aOR] 0.75; 95% confidence interval [95% CI] 0.63–0.90) less likely to have had any antenatal care and 15% (aOR 0.85; 95% CI 0.80–0.90) less likely to have had a routine postnatal check‐up. They were 4% (aOR 1.04; 95% CI 0.99–1.10) more likely to have had an antenatal hospital admission, 7% (aOR 1.07; 95% CI 0.99–1.16) more likely to have been transferred during labour and 4% (aOR 1.04; 95% CI 0.99–1.09) more likely to have had a caesarean birth, although these results were not statistically significant. With decreasing socio‐economic position women were more likely to report that they were not treated respectfully or spoken to in a way they could understand by doctors and midwives. Conclusions This analysis suggests the need for a focusing of professionals and services towards pregnant women from lower socio‐economic groups and more targeted maternal public health education towards socially disadvantaged women.